Radiation Therapy for Locally Recurrent Breast Cancer. (3rd October 2012) - Siglin, Joshua; Champ, Colin E.; Vakhnenko, Yelena; Anne, Pramila R.; Simone, Nicole L.
Abstract : Approximately one-third of all breast cancer patients experience local recurrence of their tumor after initial treatment. As initial treatment often employs the use of radiation therapy (RT), the standard of care for local breast cancer recurrence after initial breast conserving therapy has traditionally been surgical intervention with mastectomy. However, recent attempts to preserve the intact breast after recurrence with local excision have revealed a potential need for RT in addition to repeat breast conserving surgery as rates of local failure with resection alone remain high. Additionally, local recurrence following initial mastectomy and chest wall RT can be treated with reirradiation to increase local control. Repeating RT, however, in a previously irradiated area, is a complex treatment strategy, as the clinician must carefully balance maximizing treatment effectiveness while minimizing treatment-related toxicity. As a result, physicians have been hesitant to treat recurrent disease with repeat RT with limited data. Results from the current literature are promising and current clinical trials are underway to explore reirradiation modalities which will provide additional information on treatment-related toxicity and outcomes. This paper will review the current literature on repeat radiation therapy for locally recurrent breast cancer.